Adolescent income and binge drinking initiation: prospective evidence from the MyLife study. (29th October 2020) - Brunborg, Geir Scott; von Soest, Tilmann; Burdzovic Andreas, Jasmina
Abstract: Background and aims: No previous studies have examined the prospective association between disposable income and binge‐drinking initiation among adolescents. We aimed to examine whether there is such an association and, if so, whether it is robust to confounders, uniform across individual characteristics and linear versus non‐linear. Design: Prospective study of adolescents from 32 middle schools, stratified according to geographic location, urban and rural locations and standard of living. Adolescents were assessed in 2017 (T1) and 1 year later (T2). Setting: Norway. Participants: A nation‐wide sample of 1845 adolescents (mean age 13.5 years, 44% boys) with no binge‐drinking experience at T1. Measurements: Data were collected on binge drinking at T1 and T2. Data on disposable income and on a range of demographic, individual and family factors were collected at T1. Findings: Overall, 7.2% initiated binge drinking between T1 and T2. Logistic regression showed that the crude linear effect of disposable income on binge drinking initiation was substantial, and only slightly attenuated in the fully adjusted model including all putative confounders [odds ratio (OR) = 1.19, 95% confidence interval (CI) = 1.08, 1.31, P  < 0.001]. However, interaction analyses showed disposable income to be negatively related to binge drinking initiation for adolescents who had experienced light drinking at T1 (OR = 0.66, 95% CI = 0.49, 0.89, P  = 0.006) or who had seen their mothers intoxicated [OR = 0.62, 95% CI = 0.39, 0.99, P  = 0.043). Conclusion: Norwegian adolescents with higher disposable income have a greater risk of subsequent binge drinking initiation than those with lower disposable income. Each additional 100 NOK (≈ €10) of weekly income increased the risk of binge drinking initiation in the following year by approximately 20%.